PENGARUH SISTEM INFORMASI DAN KOMITMEN MANAJEMEN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Umitasari, Yessi; Rihardjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine empirically the influence of the information system and managementcommitment to the performance accountability on the work unit of Surabaya City Government. The qualitativemethod is applied in this research. The population is the apparatus of Surabaya City Government which areaspread across 40 Local Apparatus Work Units (SKPD). The sample collection techique has been done by usingpurposive sampling method. The data has been obtained by issuing questionnaires and the samples area 168people. The data analysis techiqur has been done by using the multiple linear regressions analysis. The result ofthe research shows that the information system has influence to the performance accountability on the work unitof Surabaya City Government or the management has influence to the performance accountability on the workunit of Surabaya City Government.Keywords: information system, management commitment and performance accountability